(untitled) (Journal of Partial Differential Equations, 1998)
In this paper we consider the propagation of microlocal regularity near constant multiple characteristic or a real solution u ∈ H^s (s > m + maxμ, 2 + n2)or non-linear partial differential equation F(x, u,…, ∂^βu,…)_(|β|≤m) = 0 We will prove that the microlocal regularity ncar constant multiple characteristic of the solution u will propagate along bicharacteristic with constant multiplicity μ and have loss of smoothness up to order μ - 1 under Levi condition.